Pre-Liver Transplantation Evaluation and Listing - Pan, Alexander; Koppe, Sean (Digestive Disease Interventions, 2019)
Liver transplantation provides a curative treatment option for patients with both acute and chronic liver disease, but the decision to list a patient for transplant should be an informed one to maximize post-transplantation benefit and survivability. Potential candidates meeting transplantation indications must undergo a comprehensive evaluation consisting of both physical, as well as psychiatric, assessment to be considered for transplantation. Once listed, a candidate's place on the liver transplant waiting list is determined predominantly by his or her Model for End-Stage Liver Disease (MELD)-Na score, which is a reliable tool to stratify short-term survival risk. The severity of certain conditions, however, is not accurately reflected by the MELD-Na score, and these particular diagnoses may be assigned MELD exception points. Herein, we discuss common indications for liver transplantation: the MELD system and its exceptions, the physical and psychosocial evaluation of potential transplant candidates, and some limitations of the current organ allocation system and efforts to reduce disparity in organ distribution.
Keywords: liver transplantation; MELD; MELD exception; hepatocellular carcinoma; Milan criteria; downstaging